Analysis of Determinant Factors Affecting the Behavior of Intensive Care Nurses about Ventilator-Associated Pneumonia (VAP) Bundle Care - Nani Andriani; Nurhidayah, Rika Endah; Amira Permatasari Tarigan (Talenta Publisher, 2024)
Ventilator-associated pneumonia (VAP) commonly arises due to the use of invasive endotracheal tubes, which facilitate the entry of bacteria into the respiratory system. VAP typically develops after a patient has been on mechanical ventilation for more than 48 hours. This study aims to analyze the determinant factors influencing the behavior of intensive care unit (ICU) nurses regarding VAP management at a General Hospital in Medan, Indonesia. The study employed a quantitative research approach with a survey design, involving 56 ICU nurses. The results of the multivariate analysis indicated significant p-values for the variables of education (p = 0.014), length of work experience (p = 0.004), and training (p = 0.013), demonstrating their collective influence on ICU nurses’ behaviors toward implementing VAP bundle care. Among these factors, the availability of facilities emerged as the most significant determinant, with the highest odds ratio (OR = 3.486). Nurses who had received training were 3.486 times more likely to exhibit appropriate behavior when providing VAP bundle care interventions compared to those who had not undergone such training. Based on these findings, it is recommended that every ICU nurse enhance their skills and knowledge through comprehensive training programs on VAP bundle care.